Spatial and Vertical Benthic Foraminifera Diversity in the Oxygen Minimum Zone of Mejillones Bay, Northern Chile - Tavera Martínez, Laura; Marchant, Margarita; Muñoz, Praxedes; Abdala Díaz, Roberto T. (Frontiers in Marine Science, 2022)
Mejillones Bay is located in northern Chile (23°S) and is influenced by an Oxygen Minimum Zone (OMZ), with oxygen levels below 0.5 ml l-1. This area presents particular ecological characteristics, such as circulation of currents, hotspot, high productivity and industrial activity. This ecosystem generates the need to understand their dynamics and changes across time and space, as well as to identify the differences with other OMZs. For this reason, we studied the benthic foraminifera to use them as environmental and oxygenation proxies. For this purpose, two sediment cores were collected, obtaining 14 samples of the first eight centimeters (vertical distribution), and 18 samples with a mini boxcore (spatial distribution). When analyzing the foraminifera community, some similarities were found with other OMZs,(species typical of hypoxia and angular-asymmetric morphologies). However, the Mejillones Bay recorded a particular spatial and vertical dynamics respect to others OMZs, due to presence of other species of Bolivinids not reported for this area before, and a high abundance of Buliminella elegantissima, which is not recorded in most of OMZs. Foraminifera with rounded-symmetric morphologies were present and dominant in deeper layers, reflecting a turbulent and high-energy environment. On the basis of depth and conditions of microxia or dysoxia, no significative pattern of spatial and vertical distribution was observed. The latter can be explained by local factors such as cyclonic and anticyclonic whirlpools, wastewater from industrial activity and natural events such a Tsunami occurred in 1877. These factors contributed to the mixture of the benthic foraminifera and prevented the formation of spatial and temporal patterns. Finally, an inverted TROX model was identified, indicating an apparent intensification of hypoxia (microxia: 0,01 ml l-1) in the superficial layers (0-3 cm from years 1996 to 2012), while the deeper layers (4-8 cm from years 1985 to 1877) presented foraminiferal species that indicated dysoxia conditions (0,07 ml l-1). The latter differs from other OMZs, which show a common TROX model. This study represents the first ecological reconstruction using benthic foraminifera proxies for the Mejillones Bay, which results indicate an OMZ with ecological and environmental features that differ from other OMZs.